The Roman Inquisition : A Papal Bureaucracy and Its Laws in the Age of Galileo - Mayer, Thomas F. (Thomas Frederick), 1951-2014 (Book collections on Project MUSE., 2013)
As Thomas F. Mayer demonstrates in this first study of the Roman Inquisition as an institution, the Inquisition underwent constant modification as it expanded. Originally aimed to eradicate Protestant heresy, it went beyond medieval antecedents by becoming a highly articulated centralized organ directly dependent on the pope.